A Modelling Approach for the Analysis of Underwater Explosive Performance Trials. Issue 12 (20th October 2021) - Milne, Andrew G.; Milne, Alec M.; Burn, Andrew; Carr, Andrew; Thomson, Murray
Abstract: We present here a coupled experimental and numerical modelling study to compare the underwater performance of different explosive charge types in simple geometries with a view to having confidence in the use of these models in the design of more complex warheads. Numerical modelling is used to predict the shock and bubble performance of underwater detonated charges and is intended to be used for comparison of the performance of different charge compositions. Model predictions are compared to experimental data from the underwater detonation of 1 kg cylindrical charges. It is shown that a simple 1D spherical geometry Eulerian hydrocode solution is suitable for comparison of the performance of different charge types provided that gauges are located on the radial axis of the charge and located a sufficient distance from the charge. Predictions using our chosen explosive models are shown to accurately capture the shock and bubble performance of ideal and non‐ideal charges tested and the effects of charge casing so that these models can be used in more complex warhead design studies at a later date. Abstract :